Quaternary fauna of bats in Spain: Paleoecologic and biogeographic interest - Sevilla García, María Paloma (Charles University Pres, 1989)
The study of fossil bat material collected in Quaternary localities in Spain has yielded interesting information on the characteristics of this fauna during the Pleistocene and Holocene in Spain. Out of the 25 species of Chiroptera actually living in Spain, 15 have been detected from the Middle Pleistocene onwards: Rhinolophus ferrumequinum, R. euryale, R. mehelyi, R. hipposideros, Myotis myotis, M. bechsteini, M. nattereri, M. emarginatus, Plecotus austriacus, Eptesicus serotinus, Barbastella barbastellus, Nyctalus leisleri, N. lasiopterus, Pipistrellus pipistrellus, and Miniopterus schreibersi. The presence of Myotis blythi and Plecotus auritus, quite common in the rest of Europe during the Pleistocene, and actually present in Spain, cannot be ascertained up to the Holocene. No important morphologic or metric differences with the corresponding extant species have been observed; thus we conclude that the use of bats for biostratigraphical purposes during the Quaternary is very limited. On the other hand, important changes have been observed in the geographical distribution of some species in the Quaternary, compared to the present one; these changes can be interpreted in paleoecologica1 terms. The study of the association of bat species present in a locality can provide important paleoclimatic information as well. Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub